The relationship between childhood trauma in mothers and maternal-fetal attachment: A scoping review - Abuk, Elfrida Yustina; Suryaningsih, Endang Koni; Mufdlilah, Mufdlilah (Journal of Health Technology Assessment in Midwifery, 2024)
An unpleasant childhood experience for a mother can be a risk factor that negatively impacts both the mother herself and her offspring. This review highlights the complexity and significant impact of childhood trauma on the maternal-fetal attachment relationship, emphasizing the need for a holistic approach in supporting maternal well-being and the positive development of the baby being conceived. The objectives of this review were (1) to identify the factors that affect the maternal-fetal attachment relationship, (2) to find out the relationship between childhood trauma in mothers and maternal-fetal attachment, (3) to identify the supporting and inhibiting factors of childhood trauma that affect maternal-fetal attachment.  The databases used in the search literature include Ebsco, Willey, PubMed, and ScienceDirect with articles from 2019 to 2023.The databases used in the search for lie tarur include Ebsco, Willey, PubMed, and ScienceDirect with articles from 2019 to 2023. Critical appraisal uses JBI's checklist, which includes all articles in category A. Seven articles are included in the inclusion criteria. The four themes obtained were the influence of the emotional environment on maternal-fetal attachment, sociodemographic characteristics, the relationship between maternal-fetal attachment and postnatal development, and the measurement of the relationship between prenatal, depression, and anxiety in mothers. The conclusion of this review is that maternal attachment during pregnancy plays an important role in predicting a child's emotional health and development, which emphasizes the need for holistic mental health care and adequate social support to reduce the negative impact of childhood trauma.